2014
DOI: 10.1098/rstb.2013.0234
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid signalling determines susceptibility of bundle sheath cells to photoinhibition in high light-exposed Arabidopsis leaves

Abstract: The rapid induction of the bundle sheath cell (BSC)-specific expression of ASCORBATE PEROXIDASE2 ( APX2 ) in high light (HL)-exposed leaves of Arabidopsis thaliana is, in part, regulated by the hormone abscisic acid (ABA) produced by vascular parenchyma cells. In this study, we provide more details of the ABA signalling that regulates APX2 expression and consider its importance in the photosynthetic responses of BSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…This could mean that H 2 O 2 -mediated control of APX2 expression in bundle sheath cells is fundamentally different from that in other leaf tissues (Bechtold et al, 2008). In fact, recent work using differential photosynthetic changes to different chemical treatments demonstrates ABA, APX2, and H 2 O 2 responses are distinct to BSCs compared to mesophyll (Suzuki et al, 2013;Gorecka et al, 2014). In Oryza sativa, altering NADPH/NADP + levels through C 4 -like photosynthesis in BSCs promoted HL stress responses specific to the midvein (Shen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This could mean that H 2 O 2 -mediated control of APX2 expression in bundle sheath cells is fundamentally different from that in other leaf tissues (Bechtold et al, 2008). In fact, recent work using differential photosynthetic changes to different chemical treatments demonstrates ABA, APX2, and H 2 O 2 responses are distinct to BSCs compared to mesophyll (Suzuki et al, 2013;Gorecka et al, 2014). In Oryza sativa, altering NADPH/NADP + levels through C 4 -like photosynthesis in BSCs promoted HL stress responses specific to the midvein (Shen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution images of the chlorophyll fluorescence (CF) parameter F v ′/F m ′ (PSII operating efficiency) in epidermal and mesophyll chloroplasts were obtained as described previously 64 using a Micro-FluorCam (Photon System Instruments, Czech Republic). Briefly, a single disc was placed onto the microscope slide, overlaid with a coverslip.…”
Section: Methodsmentioning
confidence: 99%
“…The ABA-dependent responses to high light stress were found to occur in detached leaves as well as whole plants, suggesting that they are leaf autonomous and do not involve ABA biosynthesis in roots. Gorecka et al (2014) have further observed that ABA signaling mutants have an effect on bundle sheath cell responses in terms of APX2 gene expression and photosynthetic efficiency of these cells, but no effect could be detected at the whole leaf level for any of the signaling mutants in response to high light, despite a series of microarray experiments and extensive physiological analysis. These results suggested that in terms of cell autonomy under high light conditions, systemic responses might be confined to bundle sheath cells and guard cells.…”
Section: Integrating the Ros-calcium Wave With Abamentioning
confidence: 99%